Estimating population size and observation bias for spring Chinook Salmon. Issue 11 (8th October 2019) - Murdoch, Andrew R.; Frady, Charles H.; Hughes, Michael S.; See, Kevin
Abstract: The primary conservation prioritization tool for spring Chinook Salmon ( Oncorhynchus tshawytscha ), population viability analysis, is often conducted with biased spawner abundance data with no associated statistical uncertainty or error. This study estimated observation error of surveyors counting redds in two spring Chinook Salmon populations where hatchery supplementation is implemented as a conservation tool. Habitat complexity, redd density and the amount of observer experience were important in estimating error rates. Increases in both habitat complexity and experience reduced net error rates. Conversely, net error rates increased as redd density increased. Unbiased estimates of redd abundance were generated and converted to spawner abundance using population specific redd expansion factors. The precision (i.e., coefficient of variation [CV]) of spawner abundance estimates were similar in the Wenatchee (natural CV = 5%; hatchery CV = 6%) and Methow (natural CV = 5%; hatchery CV = 2%) watersheds because average net error rates were similar (Wenatchee = −0.1512; Methow = −0.1748). This study addresses a criticism of population viability analysis (i.e., parameter uncertainty) that should result in more scientifically defensible conservation priorities and recommendations that can be implemented with greater certainty.